2019
DOI: 10.1111/pre.12384
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of laminarialean zoospores in seawater by real‐time PCR

Abstract: Laminarialean plants undergo heteromorphic alternation of generations between the macroscopic diploid sporophyte and the microscopic haploid gametophyte. The generations change through the formation and release of asexual or sexual reproductive cells. It is difficult to monitor the release and diffusion of zoospores into the environment. Furthermore, even if zoospores can be detected, species identification remains difficult. This study attempted to develop a sensitive and fast identification method for lamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, Nagasato et al. (2019) successfully quantified in vivo Saccharina japonica zoospore releases for the first time and found that over a period of 2 years, clear peaks occurred in October/November with undulations and slight increases above baseline of zoospore concentrations during spring in both years, supporting the seasonal lag hypothesis. The possibility of biannual fertilization events is also supported by the fact that spores and the microscopic forms of many macroalgal species have strong tolerances to long periods of darkness (Santelices et al.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, Nagasato et al. (2019) successfully quantified in vivo Saccharina japonica zoospore releases for the first time and found that over a period of 2 years, clear peaks occurred in October/November with undulations and slight increases above baseline of zoospore concentrations during spring in both years, supporting the seasonal lag hypothesis. The possibility of biannual fertilization events is also supported by the fact that spores and the microscopic forms of many macroalgal species have strong tolerances to long periods of darkness (Santelices et al.…”
Section: Discussionmentioning
confidence: 90%
“…The application of qPCR in ecological studies is well established and also used in seaweed cultivation. For instance qPCR can be used to detect and quantify reproductive material of seaweed (zoospores) in seawater (eDNA samples) (Nagasato et al, 2020). It can also be used as a tool to detect seaweed pathogens (Bernard et al, 2018).…”
Section: How To Measure Ecosystem Responsementioning
confidence: 99%
“…Druehl and Hsiao (1973) even described seasonal events that are consistent with our described seasonal lag hypothesis, with two peaks in new macroscopic sporophyte production closely matching the periods in which increased gametophyte reproduction is predicted by our hypothesis. Furthermore, Nagasato et al (2019) successfully quantified in vivo S. japonica zoospore releases for the first time, and found that over a period of two years, clear peaks occurred in October/ November with undulations and slight increases above baseline of zoospore concentrations during spring in both years, supporting the seasonal lag hypothesis. The possibility of biannual fertilization events is also supported by the fact that spores and the microscopic forms of many macroalgal species have strong tolerances to long periods of darkness (Santelices et al 2002), suitable to survive winter conditions.…”
Section: Discussionmentioning
confidence: 62%